Prediction and verification of the influence of the rs367781716 SN P on the interaction of ТАТА -binding protein with the promoter of the human АВСА9 gene - O. V. Arkova; I. A. Drachkova; T. V. Arshinova; D. A. Rasskazov; V. V. Suslov; P. M. Ponomarenko; M. P. Ponomarenko; N. A. Kolchanov; L. K. Savinkova (Вавиловский журнал генетики и селекции)
The high-throughput sequencing project “1 000 Genomes” made it possible to catalog and utilize genetic loci and single nucleotide polymorphisms (SNPs) in medicine. Analysis of SNP markers (significantly frequent differences of individual genomes of patients from the reference human genome) allows physicians to optimize treatment. On the other hand, tens of millions of unannotated SNPs correspond to a gigantic number of false positive (false negative) candidate SNP markers that are selected by computer methods for comparison of their frequency in patients with that in healthy people. This approach contributes to undervaluation of clinically relevant SNPs and to unnecessary computational expenses (on verification of neutral SNPs). Preclinical empirical verification of possible candidate SNP markers may eliminate neutral SNPs from the dataset. In the present study, we found, using the SNP_TATA_Comparator web service, the unannotated SNP rs367781716: the substitution of ancestral T (health) with minor C at position –37 before the transcription initiation site of the АВСА9 gene. This SNP significantly reduces affinity of TATAbinding protein (TBP) for this gene’s promoter and corresponds to a deficiency (low protein level) of the АВСА9 gene product (the transporter ATP-binding cassette A9) in patients with the –37C allele. For preclinical empirical verification of rs367781716, we used an electrophoretic mobility shift assay (EMSA) to measure the rates of formation (ka) and decay (kd) of the complexes of TBP with an oligonucleotide matching either allele –37C or –37T of the АВСА9 gene. We found that the rate of formation (ka) of the TBP/TATA complex for the minor allele is 2.4-fold lower than that for the ancestral allele. We calculated the empirical value of the change in the equilibrium constant of dissociation (KD = kd /ka), which characterizes binding affinity of TBP for a promoter containing the ТАТА box. This empirical value matched the value predicted by SNP_ТАТА _Comparator within the margin of error of the measurements and calculations. We also determined the half-life and Gibbs free energy of the complex of TBP with the АВСА9 promoter. Possible phenotypic manifestations of the candidate SNP marker rs367781716 are discussed.